2021
DOI: 10.1083/jcb.202106080
|View full text |Cite
|
Sign up to set email alerts
|

Sarm1 activation produces cADPR to increase intra-axonal Ca++ and promote axon degeneration in PIPN

Abstract: Cancer patients frequently develop chemotherapy-induced peripheral neuropathy (CIPN), a painful and long-lasting disorder with profound somatosensory deficits. There are no effective therapies to prevent or treat this disorder. Pathologically, CIPN is characterized by a “dying-back” axonopathy that begins at intra-epidermal nerve terminals of sensory neurons and progresses in a retrograde fashion. Calcium dysregulation constitutes a critical event in CIPN, but it is not known how chemotherapies such as paclita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 70 publications
0
47
0
Order By: Relevance
“…Recent results show that SARM1 is not just a degradative NADase, but an auto-regulated signaling enzyme responsible for producing two calcium mobilizing messenger cADPR and NAADP 8, 23 . For example, in paclitaxel-induced peripheral neuropathy, SARM1 is activated to produce cADPR, resulting in calcium increase and AxD 17 . We and others have shown that the enzyme activities of SARM1 are specifically activated by NMN 8, 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results show that SARM1 is not just a degradative NADase, but an auto-regulated signaling enzyme responsible for producing two calcium mobilizing messenger cADPR and NAADP 8, 23 . For example, in paclitaxel-induced peripheral neuropathy, SARM1 is activated to produce cADPR, resulting in calcium increase and AxD 17 . We and others have shown that the enzyme activities of SARM1 are specifically activated by NMN 8, 11 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to NADase activity, it also catalyzes the production of two calciummobilizing messengers, cyclic ADP-ribose (cADPR) and nicotinic acid adenine dinucleotide phosphate (NAADP) 8,[14][15][16] . In paclitaxel-induced peripheral neuropathy, SARM1 is activated to produce cADPR, which in turn elevates cellular calcium, resulting in AxD 17 . SARM1 is mainly expressed in neurons 18 , but can be found in variety of cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal injury or toxicity causes a reduction in NMNAT2 levels due to its rapid turnover, short half-life and the impairment of axonal transport to distal axons [ 188 ], leading to an increase in NMN:NAD + , which favours the activation of SARM1. While the impact of SARM1 on subsequent pathways is yet to be fully understood, it is thought that its activation leads to calcium influx into the axoplasm of injured axons and the breakdown of neuronal elements [ 189 , 190 , 191 ].…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%
“…In SARM1-knockout mice, the development of typical neuropathic findings such as mechanical and cold hypersensitivity in oxaliplatin [ 192 ] and the loss of intraepidermal nerve fibres following paclitaxel treatment were prevented [ 193 , 194 ]. Antagonising cyclic adenosine diphosphate ribose (cADPR), a by-product of SARM1-induced axonal degeneration, with intraperitoneal injection of 8-Br-cADPR, attenuated paclitaxel-induced mechanical hypersensitivity and partially protected against the loss of intraepidermal innervation in mice, without interfering with the antitumoral effects of paclitaxel [ 191 ]. This neuroprotective impact is attributed to reduction in axonal calcium flux or inactivation of SARM1.…”
Section: Chemotherapy-induced Peripheral Neuropathymentioning
confidence: 99%
See 1 more Smart Citation